Implications influencing the productive performance, characteristics of the carcass and meat of cattle in feedlot - Martínez, Esmeralda Desdémona (2023)
The fattening of cattle in feedlots is an option to add value to cattle reared on pastures, where an accelerated fattening of the animals is achieved in a short period of time, improving the characteristics of the carcass and the meat, while allowing the recovery of pastures during the dry season by reducing the stocking rate preserving the grassland ecosystem. However, it is necessary to have clear knowledge of the implications that influence these characteristics such as age, breed, sex, temperament, feeding, use of additives, disease prevention and control, animal welfare, buller steer syndrome and facilities in corrals. Likewise, maintain the system sustainability by reducing methane emissions from animals without affecting the quality of the meat produced. Therefore, the objective of this literature review is to present the implications that influence the productive performance, characteristics of the carcass and the meat of cattle fattened in feedlots.